Normative Vagueness of the 'Aggrieved Party' Concept and Legal Protection for Notaries under Administrative Oversight: Kekaburan Norma "Pihak yang Dirugikan" dan Perlindungan Hukum Notaris dalam Pengawasan Administratif - Meliona, Vevi; Yahya, Taufik; Suryahartati, Dwi (Mendapo: Journal of Administrative Law, 2026)
The ambiguity of the term aggrieved party in Article 7 paragraph (1) of the Minister of Law and Human Rights Regulation Number 15 of 2020 has generated legal uncertainty in Indonesia's notarial supervisory system, particularly regarding the legal standing of complainants and the protection of notaries against administrative sanctions. This study aims to examine the normative ambiguity of the provision and its implications for legal protection afforded to notaries. Employing normative legal research, the study applies statutory, conceptual, and case approaches by analyzing Jakarta Administrative Court Decision Number 25/G/2025/PTUN.JKT and Decision Number 235/G/2019/PTUN.JKT together with their subsequent judicial proceedings. The analysis demonstrates that the absence of clear legal criteria regarding the status of an aggrieved party enables complaints from individuals lacking direct legal interest, thereby increasing the risk of unlawful administrative sanctions and undermining due process of law. The findings further reveal that the Administrative Court plays a significant role in providing repressive legal protection by reviewing administrative decisions based on legality, procedural fairness, and the General Principles of Good Governance. The novelty of this research lies in proposing normative criteria for determining the legal standing of complainants and introducing a mandatory verification mechanism at the preliminary examination stage. The study concludes that clarifying the concept of an aggrieved party through regulatory reform is essential to strengthen legal certainty, ensure balanced administrative supervision, and provide effective legal protection for notaries.